Sign in
Please select an account to continue using cracku.in
↓ →
If $$5\sqrt{5}x^3 + 2\sqrt{2}y^3 = (Ax + \sqrt{2}y)(Bx^2 + 2y^2 + Cxy)$$, then the value of $$(A^2 + B^2 - C^2 )$$ is:
$$5\sqrt{5}x^3 + 2\sqrt{2}y^3 = (Ax + \sqrt{2}y)(Bx^2 + 2y^2 + Cxy)$$
$$(\sqrt{5}x + \sqrt{2}y)(5x^2 + 2y^2 + \sqrt{10}xy) = (Ax + \sqrt{2}y)(Bx^2 + 2y^2 + Cxy)$$
On comparing,
A = $$\sqrt{5}$$
B = 5
C = $$\sqrt{10}$$
$$(A^2 + B^2 - C^2 )$$
= $$((\sqrt{5})^2 + 5^2 - (\sqrt{10})^2 )$$
= 5 + 25 - 10 = 20
Create a FREE account and get: